The Level Of Parents Anxiety On Physical Education Activity At Lintang City Elementry School - Andi Nova; Andrew Rinaldi Sinulingga; Andri Syahputra (IKIP Budi Utomo Malang, 2020)
The purpose of this study to determine the level of parent’s anxiety on physical education lesson at Lintang City Elementary School. This research method uses a survey and collect the data by using a questionnaire. The scores obtained from questionnaires is analyzed by using quantitative descriptive analysis that converted in the form of percentages. The population the study is all parents of students and the sample is grade I , II, which they are 58 parents by using purposive sampling. The level of anxiety based on physiological factors on restless indicators during the physical education lesson is 74.3%. The level of anxiety based on psychological factors on indicators of worrying about something during physical education lesson is 71.3%, on the indicators of feeling safe and joy is 60.3%, and on the indicators of fear at 74.5%. The results of the study and discussion can be concluded that the level of parental anxiety on Physical Education was classified as high at 70.1%. in this study, the factor of parents anxiety caused by student activity, especially grade I and II as we know, during practice in this lesson so easy to get injury when the students careless.